Phytochemicals as Antimicrobials: Prospecting Himalayan Medicinal Plants as Source of Alternate Medicine to Combat Antimicrobial Resistance - Mohammad Vikas Ashraf; Shreekar Pant; M. A. Hannan Khan; Ali Asghar Shah; Sazada Siddiqui; Mouna Jeridi; Heba Waheeb Saeed Alhamdi; Shoeb Ahmad (MDPI AG, 2023)
Among all available antimicrobials, antibiotics hold a prime position in the treatment of infectious diseases. However, the emergence of antimicrobial resistance (AMR) has posed a serious threat to the effectiveness of antibiotics, resulting in increased morbidity, mortality, and escalation in healthcare costs causing a global health crisis. The overuse and misuse of antibiotics in global healthcare setups have accelerated the development and spread of AMR, leading to the emergence of multidrug-resistant (MDR) pathogens, which further limits treatment options. This creates a critical need to explore alternative approaches to combat bacterial infections. Phytochemicals have gained attention as a potential source of alternative medicine to address the challenge of AMR. Phytochemicals are structurally and functionally diverse and have multitarget antimicrobial effects, disrupting essential cellular activities. Given the promising results of plant-based antimicrobials, coupled with the slow discovery of novel antibiotics, it has become highly imperative to explore the vast repository of phytocompounds to overcome the looming catastrophe of AMR. This review summarizes the emergence of AMR towards existing antibiotics and potent phytochemicals having antimicrobial activities, along with a comprehensive overview of 123 Himalayan medicinal plants reported to possess antimicrobial phytocompounds, thus compiling the existing information that will help researchers in the exploration of phytochemicals to combat AMR.